Phase II trial of ipilimumab in melanoma patients with preexisting humoural immune response to NY-ESO-1 - Haag, Georg Martin; Zörnig, Inka; Hassel, Jessica C.; Halama, Niels; Dick, Julika; Lang, Nina; Podola, Lilli; Ziegelmeier, Claudia; Freitag, Angelika; Beckhove, Philipp; Enk, Alexander; Jäger, Dirk (European journal of cancer, 2018)
Background - Immune checkpoint therapy has dramatically changed treatment options in patients with metastatic melanoma. However, a relevant part of patients still does not respond to treatment. Data regarding the prognostic or predictive significance of preexisting immune responses against tumour antigens are conflicting. Retrospective data suggested a higher clinical benefit of ipilimumab in melanoma patients with preexisting NY-ESO-1-specific immunity. - Patients and methods - Twenty-five patients with previously untreated or treated metastatic melanoma and preexisting humoural immune response against NY-ESO-1 received ipilimumab at a dose of 10 mg/kg in week 1, 4, 7, 10 followed by 3-month maintenance treatment for a maximum of 48 weeks. Primary endpoint was the disease control rate (irCR, irPR or irSD) according to immune-related response criteria (irRC). Secondary endpoints included the disease control rate according to RECIST criteria, progression-free survival and overall survival (OS). Humoural and cellular immune responses against NY-ESO-1 were analysed from blood samples. - Results - Disease control rate according to irRC was 52%, irPR was observed in 36% of patients. Progression-free survival according to irRC was 7.8 months, according to RECIST criteria it was 2.9 months. Median OS was 22.7 months; the corresponding 1-year survival rate was 66.8%. Treatment-related grade 3 AEs occurred in 36% with no grade 4-5 AEs. No clear association was found between the presence of NY-ESO-1-specific cellular or humoural immune responses and clinical activity. - Conclusion - Ipilimumab demonstrated clinically relevant activity within this biomarker-defined population. NY-ESO-1 positivity, as a surrogate for a preexisting immune response against tumour antigens, might help identifying patients with a superior outcome from immune checkpoint blockade. Clinical trial information: NCT01216696
Gesehen am 15.08.2019